2004
DOI: 10.1007/s11934-004-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adrenocortical carcinoma: Contemporary outcomes

Abstract: Adrenocortical carcinoma is a rare cancer that historically has been associated with poor outcome. Throughout the past decades, growing experience has allowed better understanding of the natural history and optimal management of this cancer. Advances in imaging and aggressive surgical therapy have raised the outlook for recently diagnosed patients. Further improvements in survival will require more effective systemic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 49 publications
2
13
1
1
Order By: Relevance
“…Majority of the tumors was of high grade at diagnosis and their proportion has been increasing with time. While it is expected that more ACCs would be discovered at earlier stages of the disease due to the increased use of sensitive imaging studies in recent years with subsequent improvement in survival, multiple studies have shown findings to the contrary [ 2 , 7 , 11 - 13 ]. Kebebew et al and Kerkhofs et al reported no changes in the trend of the ACC cases being diagnosed mostly in advanced stages of the disease [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the tumors was of high grade at diagnosis and their proportion has been increasing with time. While it is expected that more ACCs would be discovered at earlier stages of the disease due to the increased use of sensitive imaging studies in recent years with subsequent improvement in survival, multiple studies have shown findings to the contrary [ 2 , 7 , 11 - 13 ]. Kebebew et al and Kerkhofs et al reported no changes in the trend of the ACC cases being diagnosed mostly in advanced stages of the disease [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have contradicted this finding. A recent review by Chen et al [12] analyzed studies from the Mayo Clinic, including 58 patients treated since 1980, finding that nonfunctional tumors actually had better prognosis than functional ones and a larger study population from Italy, which included 1000 patients with adrenal incidental masses, discovered by radiographic imaging that 4% of these masses were found to be ACC. This is clearly a higher incidence of ACC than reported previously.…”
Section: Biochemical Functionmentioning
confidence: 99%
“…Both IGF 1 and IGF 2 are involved in differentiation of the adrenal cortex. High levels of these factors may play a role in tumorigenesis and dedifferentiation [12].…”
Section: Tumorigenesismentioning
confidence: 99%
“…Unfortunately, most ACC patients were seen in advanced stages of the disease, which sometimes makes complete resection difficult or impossible (Pommier and Brennan, 1992;Chen et al, 2004). In out study, 4 patients lost the possibility of operations and died soon (3~10 months) after the diagnosis.…”
Section: Resultsmentioning
confidence: 95%